PELATIHAN MANAJEMEN USAHA DAN ASPEK HUKUM TEKNIS PEMBUATAN NOMOR INDUK BERUSAHA DAN PROMOSI PRODUK MELALUI MEDIA SOSIAL DAN ELEKTRONIK PADA KELOMPOK USAHA MIKRO KECIL DAN MENENGAH (UMKM) DESA CITAMAN SERANG BANTEN - Suhandi Suhandi; Ujang Hibar; Agus Lukman Hakim (Jurnal Abdimas Bina Bangsa, 2024)
This Beginner Community Service Activity (PMP) was held in Citaman Village, Ciomas Serang District, Banten. With the target of the Citaman Village Micro, Small and Medium Enterprises (UMKM) group. The problems faced by the partners, in this case the Citaman Village MSME group, namely: ), do not know information about legal aspects and digital marketing or product promotion through electronic means and social media, still lack knowledge of science and technology in running their business. The purpose of this service is to help increase the knowledge and skills of partners, in this case the Citaman Village MSME group, in implementing business management, making Business Identification Numbers (NIB) and product promotion through social and electronic media. The results of this service activity show that the Citaman Village MSME group can apply business management, can create a Business Identification Number (NIB) and can implement product promotions through social and electronic media, there is an increase in partner businesses, so that they can increase the income and economy of existing MSME group members in Citaman Village